Income distribution across ethnic groups in Malaysia: applying social accounting matrices - Saari, Mohd Yusof; Dietzenbacher, H. W. A.; Rijksuniversiteit, Groningen (University of Groningen, 2015)
This thesis contains a comprehensive analysis of income inequality across the major ethnic groups in Malaysia. Using a newly constructed social accounting matrix for Malaysia in 2000, income inequality is analyzed from three perspectives. First, explanations are provided for the low responsiveness of income inequality to the economic transformation and structural changes between 1970 and 2000. Second, an in-depth analysis examines the causes of the large income gaps between the ethnic groups in 2000. The analysis focuses on the distribution of income from different income types (including factor incomes and transfer payments), along with non-monetary aspects (such as population and employment sizes). The third perspective deals with the potential impacts of the two most important policies in Malaysia on poverty and income inequality. For growth-promoting policies it is examined whether reducing poverty in one sector can be achieved by targeting growth in other sectors. For the energy price policy, the effects of deregulating domestic petroleum prices on income distribution across ethnic groups are studied.